Proposing and Modeling an Ultrahigh Step-Up DC-DC Converter Including Two Stages Boost Converter, Switched Capacitor and Coupled Inductor - Vahid Abbasi; Milad Rezaie (مجله مدل سازی در مهندسی)
In this paper, a new ultrahigh step-up converter composed of two stages boost converter, a switched capacitor unit and coupled inductor is proposed. Secondary winding of the coupled inductor has been merged with the switched capacitor and leakage energy of the coupled inductor recycles through the output side. The structure contains two power switches which operate synchronously. The converter is compared from different points of view with the others presented in references. According to the results of the comparison, the converter boosts voltage with higher gain in comparison to the references. In addition, the converter requires smaller inductor in its input side and voltage stress on its semiconductors is low. This paper presents analysis of operation states, design of the inductors and main equations of the converter performance. To validate the analysis, results of simulation in SIMULINK MATLAB and experiments are utilized as the last section of the paper. The prototype is designed for 150W output power to boost input voltage with gain equal to 16.